Studi Kualitatif Terhadap Makna Kehilangan dan Regulasi Emosi Pada Remaja Dengan Pengalaman Motherless - Cindy Claudya; Diva Herla Aurellia; Felix Sebastian Hutagaol; Rina Mirza; Winida Marpaung (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The loss of a mother figure (motherless) is an experience that can affect adolescents’ emotional development, as mothers play a crucial role as sources of affection, emotional support, and a sense of security. The absence of a mother, whether physical or emotional, may lead to various psychological responses among adolescents. This study aimed to explore the meaning of maternal loss and the process of emotion regulation among adolescents experiencing motherless. A qualitative approach with a phenomenological method was employed. The participants consisted of three adolescents aged 15–21 years who were selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings revealed that motherless was perceived as the loss of a figure who provides attention, affection, security, and emotional support. This experience evoked various emotional responses, including sadness, anger, disappointment, jealousy, loneliness, and feelings of neglect. Nevertheless, the participants demonstrated the ability to develop emotion regulation through various adaptive strategies, such as engaging in positive activities, seeking social support, developing acceptance of their circumstances, and strengthening their relationship with God through spiritual practices. The findings also indicated that social and spiritual support played a significant role in helping adolescents cope with loss and maintain emotional stability. It can be concluded that the experience of motherless not only generates complex emotional impacts but also encourages the development of emotion regulation skills and psychological resilience as part of the adaptation process to loss.